Level of knowledge on insulin treatment and level of compliance among diabetic outpatients in Hospital Tengku Ampuan Afzan, Kuantan - Syd Amra, Syarifah Amirah; Che Yahaya, Yasmin Amirah (2013)
Insulin injection is one of the ways of medication use to overcome problems that diabetic patients have. Insulin injection is the class of medication of hormones. Its function is to replace the insulin that cannot be secreted adequately by our body. However, its effectiveness is related with patients’ knowledge and compliance on insulin treatment. So we have carry out a survey to evaluate patients knowledge about insulin treatment and also to assess their compliance towards the insulin treatment. This is our aim for this project. The objectives of this study is to study their demographic, evaluate patients understanding about insulin treatment and to assess whether patients are compliance or not with insulin treatment. The study was carried out by observational study by selecting patients randomly and request to fill the questionnaire given. The survey was conducted on 7th January 2013 and 14th January 2013 at MOPD clinic in Hospital Tengku Ampuan Afzan, Kuantan on their diabetic clinic day. From analyzed data, it can be concluded that the degree of knowledge and compliance among diabetic patients is high due to long term usage of insulin treatment. Nevertheless, they are aware of the further complications of being non-compliant and give a lot of effort to adhere with the treatment although it takes more effort.